ANALISIS SOCIAL MEDIA MARKETING DAN BRAND IMAGE TERHADAP CUSTOMER RESPONSE (STUDI KASUS PADA UMANA BALI, LXR HOTELS AND RESORTS PASCA REBRANDING) - Made Ayu Jayanti Prita Utami; Putu Wira Widiantara; Upayana Wiguna Eka Saputra (Proceeding Maritime Business Management Conference, 2024)
This study aims to analyze the influence of Social Media Marketing and Brand Image on Customer Response at Umana Bali, LXR Hotels and Resorts, following their rebranding. The research method used is a quantitative approach with a descriptive causal research type. Data were collected through questionnaires distributed to customers who follow Umana Bali’s Instagram accounts. The findings reveal that Social Media Marketing and Brand Image have a significant impact on Customer Response. Multiple linear regression analysis shows that these two variables simultaneously contribute significantly to the variability of Customer Response. These findings emphasize the importance of social media marketing strategies and brand image management in creating a positive customer experience. This study provides practical insights for the hospitality industry, particularly Umana Bali, to continuously optimize digital marketing strategies and strengthen brand image to enhance customer loyalty and purchase intent. Suggestions for future research include exploring new social media platforms and conducting comparative studies with other companies to examine broader effectiveness.